Caracterização morfodinâmica e sedimentológica das praias do Poço, Camboinha, Ponta de Mato e Miramar, município de Cabedelo, Paraíba - Monteiro, Diego Cezar da Silva (2017)
The beaches are environments naturally unstables, mainly because of the cluttered occupations that have been suffering about the latest centuries, increasing around this environments towns, balneary and many others tour activities, comercial and industrials activities. This reality has been causing increasingly shore environments disequilibrium, associated with humans tries to retain in fixed positions, buildings nearby the shore, being able to results in reductions or completely losts of this environments. In Cabedelo city, the shore dynamics and uses of areas around has been occurring without plans than can be able to intervene various impact frames. Against this problematic, this research had as a general object the shore dynamics characterization of Poço beach, Camboinha, Ponta do Manto and Miramar, as a morfology and sedimentology. The reffered area is localized in oriental edge of Paraíba state – Brazil Northeastern, more accurately in Cabedelo city. To reach the proposed object in this research, was necessery a process characterization of natural dynamics shore, subsidized by Cabedelo physics environments, the beaches morfology and sedimentology already mentioneds. To observe the beaches environments, the relations between the antropic activities and their efects on the beaches studied, stabilized camp Works, during about one year ( April 2015 to April 2016), been divided in eigth monitoring points and dados collect, two in each beach P01 and P02 on Poço beach, P03 and P04 on Camboinha beach, P05 and P06 on Ponta do Mato beach and P07 and P08 on Miramar beach. In that points was performeds shore tophographic profiles, Always performeds during the tides of syzygy, according to tides boards, reffering to Cabedelo port, as well, the sediment demonstration collects around all shore environments, either was collected hydrodynamics dados of at least two months than posteriorly provided graphic products than helped in morfology characterization, sedimentology and hydrodynamics of studied shore environments. From the researched, the beaches where the shore environments do not are preserved shows biggers indexes of erosion, having with exemple the P02 of Poço beach, wherein had been destroyed during of the research, as well the distinction of shore sectors than comprehend the beachs of Poço, Camboinha, Ponta de Mato e Miramar, where the firsts occupations characteristics were more intense, presenting waterproofing of post beaches sectors. While the others are more preserved in this matter. From the granulometric dados, it is perceived that the most of beach forehead environments samples, shows in the most majority with fine sands, poorly selected and negative asymmetries. That indicate than this compartiment suffer constant losts of sediments for the anothers compartiments., feeding the beach and the post beach. (when they exist) of profiles. The beaches sediments compartment analyzed, showed in the most of case with average sands granulometric, moderately selected to nicely selected and asymmetry varying between approximately symmetric and positives. Indicating a tendence to sedimentation of this compartiment and high energy. Anon the sediments of post beach shows characteristics of fine sand granulometrics, nicely selecteds and negative asymmetrics, indicating than that environments has in yours principal characteristic a agent who has a quite competence to transport the sediments in long of the shore profile, presentsa characteristics of eolian sedimentation. As a morfodynamics status of the analyzed beaches, both was constituted intermediary, been import betters analyzes posteriorly.